Upaya MTsS Syekh Ibrahim Harun Tiakar Dalam Mempertahankan Eksistensinya 2000-2021 - Muhammad Nur Fuad; Najmi Najmi (Jurusan Sejarah FIS UNP, 2022)
This research is a historical research on the efforts of Sheikh Ibrahim Harun Tiakar's private Tsawiyah (MTsS) adrasa in maintaining its existence. The purpose of this study is to explain how the background of the emergence of Mtss Syekh Ibrahim Harun Tiakar from Pondok Pesantren to Mtss Syekh Ibrahim Harun Tiakar. And the efforts of Mtss Sheikh Ibrahim Harun in maintaining its existence in 200-2021. The method used in this study is the historical method which consists of heuristics, criticism, interpretation, and historiography. Syekh Ibrahim Harun Tiakar Private Madrasah Tsawiyah (MTsS) Is a madrasa of pride for the Tiakar community during the Dutch period which was formerly called